2020
DOI: 10.1017/ice.2020.305
|View full text |Cite
|
Sign up to set email alerts
|

Costs of ambulatory pediatric healthcare-associated infections: Central-line–associated bloodstream infection (CLABSIs), catheter-associated urinary tract infection (CAUTIs), and surgical site infections (SSIs)

Abstract: Objective: Ambulatory healthcare-associated infections (HAIs) occur frequently in children and are associated with morbidity. Less is known about ambulatory HAI costs. This study estimated additional costs associated with pediatric ambulatory central-line–associated bloodstream infections (CLABSIs), catheter-associated urinary tract infections (CAUTI), and surgical site infections (SSIs) following ambulatory surgery. Design: Retrospective case-control study. Setting: Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although there are international recommendations for SSI prevention, it can be challenging to implement them in various clinical settings, especially in LMICs, because of a lack of resources and an unorganized infrastructure [ 42 ]. This section highlights the differences in patient outcomes between high-, medium-, and low-income nations (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are international recommendations for SSI prevention, it can be challenging to implement them in various clinical settings, especially in LMICs, because of a lack of resources and an unorganized infrastructure [ 42 ]. This section highlights the differences in patient outcomes between high-, medium-, and low-income nations (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%
“…Both qualitative and quantitative measures were analyzed, mainly using SF-36 questionnaires. According to the findings of the few studies, SSI has a considerable negative influence on patients' QoL and impacts their physical, psycho-social, and financial well-being, as well as the doctorpatient connection [40][41][42][43][44][45][46][47]. A nested case-control study at the University of Iowa Hospitals and Clinics revealed that factors like LOS before surgery and postoperative cerebrospinal fluid leak increase the risk of SSIs.…”
Section: Patient Qolmentioning
confidence: 99%
See 1 more Smart Citation
“…In its 2014 report, the National Healthcare Safety Network reported that most bloodstream infections (63.0%) and access-related bloodstream infections (69.8%) occurred in hemodialysis patients with a CVC (5). The cost of ambulatory care of CRBSI, and hospitalization of pediatric hemodialysis patients with CRBSI is substantial, ranging between $11,584-36,266 per patient, with higher costs in patients needing intensive care unit stay and CVC replacement (6,7). Microbial colonization and biofilm formation on the surface of CVC occurs frequently in hemodialysis patients dialyzed through CVC, and has been identified as a source of the microorganisms causing CRBSI (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…19 Despite unclear rates, data from the database used in this study indicated that costs of SSI following ambulatory surgery in pediatric patients were $6,370 per infection (95% confidence interval [CI], $4,022-$8,719). 20 Rates of SSI following pediatric ambulatory surgery in all surgery types and in a multicenter cohort have never been clarified, and risk factors for this type of infection as well as outcomes remain unclear. To fill this knowledge gap, we conducted a multi-institution retrospective epidemiologic study to identify and analyze incidence, risk factors, and outcomes associated with SSIs following all types of ambulatory surgery in pediatric patients.…”
mentioning
confidence: 99%